Mechanobiological Implications of Cancer Progression in Space - Kim, Hyondeog; Shin, Yun; Kim, Dong-Hwee (Frontiers in Cell and Developmental Biology, 2021)
The human body is normally adapted to maintain homeostasis in a terrestrial environment. The 14 novel conditions of a space environment introduce challenges that changes the cellular 15 response to its surroundings. Such an alteration causes physical changes in the extracellular 16 microenvironment, inducing the secretion of cytokines such as interleukin-6 (IL-6) and tumor 17 growth factor-β (TGF-β) from cancer cells to enhance cancer malignancy. Cancer is one of the 18 most prominent cell types to be affected by mechanical cues via active interaction with the 19 tumor microenvironment. However, the mechanism by which cancer cells mechanotransduce 20 in the space environment, as well as the influence of this process on human health, have not 21 been fully elucidated. Due to the growing interest in space biology, this article reviews cancer 22 cell responses to the representative conditions altered in space: microgravity, decompression, 23 and irradiation. Interestingly, cytokine and gene expression that assist in tumor survival, 24 invasive phenotypic transformation, and cancer cell proliferation are upregulated when 25 exposed to both simulated and actual space conditions. The necessity of further research on 26 space mechanobiology such as simulating more complex in vivo experiments or finding other 27 mechanical cues that may be encountered during spaceflight are emphasized.